Are they ready to teach? Student teachers' readiness for the job with reference to teacher competence frameworks. Issue 2 (15th March 2017) - Mohamed, Zulaikha; Valcke, Martin; De Wever, Bram
Abstract: This is the first report in a series of studies concerning student teachers' readiness-for-the-job, defined by a framework of 11 international teacher competences (ITCs). Attaining readiness-for-the-job is connected to four characteristics of teacher education, namely; (1) employing the ITCs in day-to-day teaching in initial teacher education, (2) integrating the ITCs in the curricula of teaching programmes, (3) exercising the ITCs through practicum at schools and (4) by teacher educators modelling the ITCs. In the present study, a student sample from four teacher education colleges ( n = 226) was surveyed to explore the extent to which students felt ready-for-the-job. The study outlines the degree to which the characteristics of teacher education are associated with student teachers' readiness-for-the-job. The results identify the critical areas to be developed in these prospective teachers before they can actually become ready-for-the-job, and especially the central role of their teacher educators in shaping their professional competence.